Groups with many Subgroups which are Commensurable with some Normal Subgroup - Ulderico Dardano; Silvana Rinauro (Advances in Group Theory and Applications, 2019)
A subgroup H of a group G is called commensurable with a normal subgroup (cn) if there is N C G such that |HN/(H ∩ N)| is finite. We characterize generalized radical groups G which have one of the following finiteness conditions: (A) the minimal condition on non-cn subgroups of G; (B) the non-cn subgroups of G fall into finitely many conjugacy classes; (C) the non-cn subgroups of G have finite rank.